PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PPKM DARURAT DI KABUPATEN GARUT - Hafadh Furqan; Theresia Febrian Sinaga; Jioanda Riza Nugraha (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2021)
The Covid-19 pandemic is increasing throughout Indonesia. Due to this, the handling of covid-19 is very important to do to overcome the spread of the covid-19 virus because if there is no handling of this virus it will endanger public health. As we know COVID-19 can cause mild to severe symptoms. There are about 80% of mild symptoms (runny nose, sore throat, cough, and fever) that do not require special treatment but there are also people who suffer from severe symptoms, such as with pneumonia or difficulty breathing, which usually appear gradually. One of the efforts to deal with COVID-19 is to implement the PPKM (Enforcement of Community Activity Restrictions) policy. None other than the goal is to foster public compliance with health protocols, prevent covid-19, and suppress the spread of COVID-19, so that the tourism and creative economy sector (tourism and creative economy) will bounce back and the economic sector will recover soon. Garut Regency is one of the regencies in Indonesia that also applies this PPKM regulation. This is the background of the author to examine the participation of the people of Garut Regency during the implementation of PPKM in an effort to handle COVID-19. This study aims to find out how the role of the people of Garut Regency and what changes occur during the implementation of PPKM in Garut Regency. The research method used is a literature study by elaborating research that is relevant to the concept of empowering local communities. In one related study, it was stated that community participation in the implementation of emergency PPKM in Garut Regency showed significant results. Therefore, through this program-based idea, we are able to achieve optimal implementation of emergency PPKM so as to increase the health status as high as possible. Keywords: Covid-19, Community Participation, PPKM, Health protocol